Pengaruh pemberian actinomycetes terhadap penurunan jumlah leukosit pada mencit diare - Ivena Claresta; Endang Sri Lestari; Gemala Anjani (Poltekkes Kemenkes Aceh, 2024)
Background: Diarrhea cases are mostly caused by enteropathogenic escherichia coli (EPEC). Elevated white blood cells or leucocytes are closely associated with the incidence of diarrhea due to bacterial infection. Actinomycetes are known to have antibacterial properties that can fight pathogenic microorganisms.Objectives: To analyze of the effectiveness of Actinomycetes from the right wing of Musca domestica on leucocyte counts in EPEC-induced mice.Methods: Experimental study with randomized post-test only with control group design. This study was conducted from June to July 2023 at the Pharmacology Laboratory of Muhammadiyah Surakarta University, using 30 mice divided into 5 groups. Actinomycetes intervention was given equivalent to 0,5 McFarland standard with dose variations: 0,26ml/20gBW (group P1), 0,65ml/20gBW (group P2), and 1,3ml/20gBW (group P3). EPEC induction was 0,5ml orally in the treatment group and negative control group (KN). The healthy control group (KS) was given 0,5ml of mineral water. The variable measured was the number of leucocytes of Mus musculus mice taken on the third day after the intervention. Data processing was performed using the Kruskall-Wallis Test to determine differences between groups with level significantly p<0,05.Results: There was a decrease in the leucocytes counts in the treatment group compared to the KN group (p=0,027). The highest mean leukocyte count was seen in the KN group (8.786,7 mm3) while, the lowest mean leukocyte count was in the P2 group (6.48,3 mm3).Conclusion: Actinomycetes intervention in EPEC-induced diarrhea mice effectively reduces leucocyte counts.KeywordActinomycetes, Leukocyte, Diarrhea